Effects of sustained elevated CO2 concentration and Nitrogen nutrition on wheat (Triticum aestivum L. cv Gamtoos) - Kgope, Barney Stephen (Rhodes University, Faculty of Science, Botany Department, 2000)
There is consensus that high CO2 results in enhanced growth and yield for most crop plants. However, most of these studies were carried out in the presence of adequate nutrients, which is also the case in agricultural systems (managed ecosystems). About 20% of the earth's land mass have sufficiently low levels of nutrients to cause some kind of stress to plants. On the other hand, elevated [CO2] decreases foliar nutrient elements in plants and as a result partitioning of certain nutrient elements in plants is altered. Little data is available on the partitioning of most nutrient elements in plants, and this will definitely impact on growth and yield. To investigate this, wheat (Triticum aestivum L. c.v. Gamtoos) was grown in controlled environment cabinets at 360 and 700 Âµmol mol -1 CO2. The full Long-Ashton nutrient solution comprising of three-nitrogen concentrations ([N]) viz. (4,6 and 12 mM) was used to water plants everyday. The measurement of net assimilation rate (NAR), stomatal conductance (gs), transpiration rate (E), water use efficiency (WUE), foliar [N], nitrogen use efficiency (NUE) and growth parameters (total plant biomass (TPB), total plant height (TPH), leaf area (LA), shoot and root dry weight) were made 7 days after germination (7 DAG) till the onset of flowering. The increase in nitrogen supply in the order of 4, 6 and 12mM resulted in an increase in NAR, g_s_ , WUE and a decline in E under elevated [CO2]. Under elevated [CO2] NAR was observed to increase during the first two weeks reaching its maximum at 14 DAG, thereafter followed by a decline reaching its maximum at 28 DAG. This was later followed by an increase at 35 DAG onwards. Under elevated [CO2], NAR was increased significantly between the nitrogen regimes during the first (7-14 DAG) and the last two (35-42 DAG) weeks. The response of assimilation as a function of internal [CO2] (Ci), showed a decrease with age at ages 14, 28 and 35 DAG. This negatively affected the initial slope and the CO2 saturated photosynthetic rates under all treatments. This suggest that acclimation may have been as a result of both stomatal and biochemical limitations. All the photosynthetic pigment levels (chl_a_, chl_b_, chl_(a+b)_, and C_(x+c)_ ) increased with an increase in nitrogen supply from 4 to 6mM [N]. A 12mM [N] resulted in a significant decline in the photosynthetic pigment levels compared to a 6mM [N]. Chla remained higher than chlb under all treatments. Also, NAR was seen to increase and decrease concomitantly with the photosynthetic pigment levels. Foliar [N] was seen to decrease with an increase in nitrogen supply from 4 to 6 mM [N] under elevated [CO2] and the effects were adverse under the 4mM [N]. Under the 6mM N regime foliar [N] was positively correlated to NAR for elevated [CO2] grown plants. Similarly, E was positively correlated to foliar [N] under the same conditions. Elevated CO2 and increase in nitrogen supply had a pronounced effect on total plant height (TPH), total plant biomass (TPB), leaf area (LA), shoot and root dry weight and nitrogen use efficiency (NUE). The effects were more pronounced under a 6mM [N] as a result of high NUE. However, under 12mM [N] growth was not as expected as a result of lower NUE. Under all treatments shoot dry weight (SDW) was positively correlated to NUE. Anatomical studies revealed that total leaf and midrib thickness was significantly increased with an increase in nitrogen supply under elevated CO2 to support the larger leaf areas. There were no significant changes in the chloroplast ultrastructure as a result of the increase in nitrogen supply and CO2 enrichment. Starch grain surface area was seen to decline with an increase in nitrogen under both ambient and elevated CO2. Elevated CO2 and increase in nitrogen supply significantly increased total grain dry weight per plant by 47 and 46% respectively under 6 and 12mM [N]. In contrast, the increase was by about 21, 61 and 67% respectively under 4, 6 and 12mM [N] between the CO2 regimes.
Keywords: Wheat -- Growth; Wheat -- Nutrition; Nitrogen fertilizers; Nitrogen in agriculture